DIDÁTICA DA HISTÓRIA E CONSCIÊNCIA HISTÓRICA: PESQUISAS NA PÓS-GRADUAÇÃO BRASILEIRA (2001-2009) - Barom, Wilian Carlos Cipriani (2012)
With this work we seek to contribute to the area of Didactics of history. To do this, we use an analysis of academic research – theses and dissertations – around the teaching of history, to identify how the concept of historical consciousness has been used. For the case of this research, the theoretical bias with which conceptualize historical consciousness refers to the peculiar array Germanic, from the trilogy entitled theory of history of the philosopher JörnRüsen. In this sense, built a first chapter in which our understanding of the concepts presented, as well as rüsenianos is a possible interrelation between these concepts around axis teaching. The second chapter was a look about the empirical data to identify how these concepts are being used in research on the teaching of history. Do not set ourselves the task of judging these appropriations regulatory concepts and underlying theory, but yes, naming trends and possibilities that were found, forms of interpretation of theory and specific contributions in the process of establishment of the area of Didactics of history, for then we trace a bird's-eye view and handling of this area. These studies examined were taken as documents, ' traces ', intentions of groups/individuals, which in turn relate in society, which inserts in the category of documentary research. Thirty-four academic works were analyzed, being ten theses and twenty-four dissertations.